Factors influence non-Muslim intention to purchase halal food products / Husna Izzati Naezam - Naezam, Husna Izzati (Faculty of Business and Management, 2018)
The purpose of this study is to identify the factors influence intention to purchase halal food products among non-Muslim in Melaka Tengah. The research is based on 150 respondents and used convenience sampling as a technique. The results show that attitude, subjective norm and perceived behavioral control have influence on intention to purchase Halal food products among non-Muslim in Melaka Tengah. In addition, attitude and subjective also give impact on intention to purchase Halal food products among non-Muslim in Melaka Tengah. The most influential factor is perceived behavioral control on intention to purchase halal food products.